Penilaian Fungsi Ventrikel Kanan Menggunakan Metoda Ekokardiografi Speckle Tracking Pada Penyakit Paru Obstruktif Kronis - Mochamad Arif Nugroho; Amiliana M Soesanto; Renan Sukmawan; Aryo S Kuncoro; Dewiana Kusmana; Poppy S Roebiono; M Munawar; Ganesja M Harimurti (The Indonesian Heart Association, 2010)
Background In daily practice, evaluation of RV useful in patients with COPD because of its affect prognostic value. Invasive and non-invasive imaging in the evaluation of RV function has several limitations because RV geometry. Speckle tracking is a modality of echocardiography. Speckle tracking can determine strain of myocardium. When compared with strain derived Tissue Doppler, Speckle tracking strain independent of angle so that the measurement of strain to be more reliable. And so far RV assessment with Speckle tracking is still a less investigated. Is there any difference between RV function on echocardiography examination using Speckle tracking methods with varying degrees of COPD?Methods Cross-sectional study conducted in 59 people with COPD who had performed spirometry examination for the classification of severity COPD. Then the patient performed an echocardiography examination using Speckle tracking methods. Then Data will analyze by testing the difference between Speckle tracking and the severity of COPD and also between Speckle track-ing and pulmonary hypertension.Result There COPD subjects 10.2% and 37.3% mild COPD subject was, with men more than women. There were no significant differences between the severity of COPD and right ventricular function using Speckle tracking method. There is a global strain value was higher in non-pulmonary hyper-tension subjects when compared with pulmonary hypertension subjects but the difference was not significant (p = 0.09).Conclusion There were no significant differences between the severity of COPD and RV function using Speckle tracking methods.